Country-level indices in predictive models of helminth infections: Perspectives from Southeast Asia. - Nathkapach Kaewpitoon Rattanapitoon; Chutharat Thanchonnang; Schawanya Kaewpitoon Rattanapitoon (PLoS Neglected Tropical Diseases, 2025)
Predictive models integrating country-level indices with individual variables offer valuable insights into soil-transmitted helminth (STH) infection risk among migrant populations. However, national indicators such as the Human Development Index and sanitation coverage may inadequately capture the heterogeneous exposure risks within and beyond countries of origin. Drawing on experiences from Southeast Asia, we highlight limitations of relying solely on aggregated metrics and emphasize the importance of incorporating post-migration factors, including living conditions and occupational exposures. Ethical considerations surrounding stigma and discrimination in nationality-based screening are also discussed. We advocate for contextual adaptation and validation of predictive frameworks to better serve diverse migrant communities and improve equitable access to parasitic disease control.